2007
DOI: 10.1007/978-3-540-76298-0_59
|View full text |Cite
|
Sign up to set email alerts
|

Matching Patient Records to Clinical Trials Using Ontologies

Abstract: Abstract. This paper describes a large case study that explores the applicability of ontology reasoning to problems in the medical domain. We investigate whether it is possible to use such reasoning to automate common clinical tasks that are currently labor intensive and error prone, and focus our case study on improving cohort selection for clinical trials. An obstacle to automating such clinical tasks is the need to bridge the semantic gulf between raw patient data, such as laboratory tests or specific medic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(51 citation statements)
references
References 10 publications
0
50
0
1
Order By: Relevance
“…In the following, we describe two methods for clinical trial recruitment [1], [13] that are based on Semantic Web technologies. Similar to our approach, both methods employ a terminology.…”
Section: Indicators and Eligibility Criteriamentioning
confidence: 99%
See 1 more Smart Citation
“…In the following, we describe two methods for clinical trial recruitment [1], [13] that are based on Semantic Web technologies. Similar to our approach, both methods employ a terminology.…”
Section: Indicators and Eligibility Criteriamentioning
confidence: 99%
“…They use the NCI ontology to represent both patient data and the eligibility criteria. Patel et al [13] demonstrated that clinical trial criteria can be formulated as description logic queries, which a reasoner can use together with SNOMED CT to infer implicit information that results in retrieving eligible patients.…”
Section: Indicators and Eligibility Criteriamentioning
confidence: 99%
“…In collaboration with Columbia University Medical Center, we used SHER to design a solution for the problem of finding matching patient records for clinical trials criteria [10]. Currently, there are approximately 65,000 clinical trials that are designed to test various drugs and proce-250 dures.…”
Section: Semantic Querying Of Patient Recordsmentioning
confidence: 99%
“…In this way, query answering turns into logical deduction. From a logic perspective, an interesting new flavour of this application is scale: in addition to the already large Snomed CT, the logical theory now also comprises a potentially huge amount of medical data (as ground facts), and new questions arise due to the special use of deduction in this application [23,17].…”
Section: Applications and Engineeringmentioning
confidence: 99%